The impact of climate change on the increase in international conflicts and the growth of the phenomenon of terrorism (قضايا سياسية, 2025)
Many countries and places around the world witnessed security challenges that coincided with, and followed, severe climate changes and fluctuations in them, which negatively affected their food and water resources, and reduced the ability of countries to meet the needs of their people. This paved the way for the outbreak of intra-conflicts at the local level, The number of international conflicts has increased, the development of the terrorist phenomenon has increased, and the number of terrorists has increased, in addition to the increasing levels of fragility and political instability, especially in developing countries that lack the elements of response and flexibility necessary for confrontation.